Структурно-динамічні особливості станів психічного виснаження у студентів медичного закладу вищої освіти - Єфіменко, Сергій Олегович; Yefimenko, S. O. (My University, 2023)
Аналіз актуальних літературних джерел дає можливість сформувати уявлення, що незважаючи на значну поширеність станів психічного виснаження, бракує репрезентативної науково обґрунтованої інформації щодо структурно-динамічних особливостей досліджуваних станів у контингенту студентів медичних закладів вищої освіти. Мета: за допомогою клініко-психопатологічного аналізу проявів психічного виснаження у студентів медичного закладу вищої освіти встановити структурно-динамічні особливості цих станів. Методи, що були використані: клініко-психопатологічний, психодіагностичний та клініко- статистичний. За результатами дослідження встановлено, що прояви психічного виснаження в обраного контингенту характеризувалися значною поширеністю, що сягала 54,0 %, клінічним поліморфізмом та інтрагруповою гетерогенністю, істотною представленістю порушень інтерперсональної чутливості (61 (34,8 %) студент) та психотизму (73 (41,7 %) студенти), проявів обсесивно-компульсивного (47 (26,8 %) студентів) та депресивного (49 (28,0 %) студентів) спектрів. Встановлено п'ять варіантів найпоширеніших поєднань психопатологічних феноменів різних спектрів: депресивного та обсесивно-компульсивного (46 (26,3 %) студентів), ворожості та психотизму (41 (23,4 %) студент), психотизму та проявів інтерперсональної чутливості (30 (17,1 %) студентів), проявів інтерперсональної чутливості та тривоги (29 (16,6 %) студентів), соматичної заклопотаності та фобічних проявів (21 (12,0 %) студент). The analysis of relevant literary sources makes it possible to form the idea that, despite the significant representation of states of mental exhaustion, there is a lack of representative evidence-based information about the structural and dynamic features of the studied phenomena in the contingent of medical students. Purpose. By means of clinical-psychopathological analysis of the manifestations of mental exhaustion in medical students, to establish the structural and dynamic features of these conditions. Methods that were used: clinical-psychopathological, psychodiagnostics and clinical-statistical. According to the results of the study, it was found that the phenomena of mental exhaustion in the formed contingent were characterized by: a wide prevalence, reaching 54.0 %, clinical polymorphism and intragroup heterogeneity, a significant representation of interpersonal sensitivity disorders (61 (34.8 %) students) and psychotism (73 (41.7 %) students), manifestations of obsessive-compulsive (47 (26.8 %) students) and depressive (49 (28.0 %) students) spectra. Five variants of the most common compilations of psychopathological phenomena of various spectra were established: depressive and obsessive-compulsive (46 (26.3 %) students), hostility and psychotism (41 (23.4 %) students), psychotism and manifestations of interpersonal sensitivity (30 (17.1 %) of students), manifestations of interpersonal sensitivity and anxiety (29 (16.6 %) students), somatic anxiety and phobic manifestations (21 (12.0 %) students). The representation and structural-dynamic features of states of mental exhaustion in medical students have been established, which gives a better understanding of the pathogenesis of these conditions and forms the basis for their systematization.
Structural-dynamic features of states of mental exhaustion in medical students
Keywords: психічне виснаження; емоційне вигоряння; дезадаптація; студенти; психотерапія; mental exhaustion; emotional burnout; maladaptation; students; psychotherapy